Efektifitas Kinerja Pada Bidang Pemenuhan Hak Anak Dinas Pmberdayaan Perempuan dan Perlindungan Anak Kota Bekasi - Rizaldi Rizaldi; Dadan Kurniansyah; Dewi Noor Azizah (Peneliti.net, 2022)
The concept of effectiveness is a condition that indicates the level of success or achievement a person or organization, as measured by the quality, quantity, and time of previous plans. In other words, the more successful plans implemented, the more effective the campaign Performance is the result of work done by a person or group people in an organization, according to their authority and responsibility respectively, to lawfully and not against the law achieve their goals the organization concerned. Morality and Ethics. Therefore, the performance is important for a company or organization. The main mission of the Service Women's Empowerment and Child Protection in Bekasi City is to assist the Mayor in lead, control and coordinate the administration of government affairs and services that are the main tasks of the Office of Gender Mainstreaming (PUG), Empowerment and Family Quality (PKK), Achievement of Children's Rights (PHA), and in some areas, especially in Bekasi City, Prevention and Management of Violence Against Women and Children (PKTPA), to achieve the vision and mission.